Exploring the Relationship between Meaning in Life and Psychological Distress in Male Patients with Substance Use Disorder in Pakistan - Mufti, Ali Ahsan; Kamal, Muhammad Asif; Huma, Shafqat; Qasim, Muhammmad Fahim; Fatima Amir Khan; Ahmed, Hussain (Journal of Pakistan Psychiatric Society, 2025)
Objectives: To assess relationship between psychological discomfort and life’s purpose in Pakistani men with drug use disorders. Study design: Correlational Study Place and duration of study: The study was conducted at Bacha Khan Medical Complex/Gajju Khan Medical College Swabi in a duration of 5 months from march 2023 to July 2023. Subjects and methods: One hundred male participants with a diagnosis of Substance use disorder (SUD) who were 18 years old were included in the research from local clinics and treatment facilities for addiction treatment and rehabilitation centers. Informed consent was taken from the participants. Psychological discomfort and sense of purpose were measured through The Purpose in Life Test (PIL) and the Brief Symptom Inventory (BSI) respectively. Results: The results showed that participants’ average age was 35.4 years (SD = 8.6) while average duration of drugs use was 9.2 years (SD = 4.3). The psychological distress among individuals was moderate, with a mean BSI score of 2.3 (SD = 0.7). The average PIL score was 42.1 (SD = 9.6), which indicated a moderate degree of life meaning.